Enhancement of students’ mathematical connection through Knisley mathematics learning model assisted by GeoGebra - Ichtiari, Atina Rahmah; Fisher, Dahlia; Rahman, Taufik; Yatim, Siti Ainor Mohd (Jurnal Elemen, 2024)
This study aims to determine whether the increase in the mathematical connections of students who receive the Knisley mathematics learning model is higher than students who receive conventional learning models. The method used in this study was a quasi-experimental design with a nonequivalent control group. This study involved two classes: an experimental class and a control class. Students in the experimental class learned with the Knisley mathematics learning model assisted by GeoGebra, while students in the control class received learning with conventional learning models. This research involved 50 students in class. The study was conducted with the object of this research, which is the ninth grader students in one of the public junior high schools in Bandung. The results showed that the increase in the mathematical connections of students who received the Knisley mathematics learning model was more elevated than that of students who received conventional learning. Knisley's mathematics learning model provides space for students to build their knowledge and can facilitate students in fulfilling mathematical connection indicators. Learning using GeoGebra can increase student enthusiasm. Student activeness in learning can be increased by applying the GeoGebra-assisted Knisley mathematics learning model.